MAKNA SIMBOLIS DAN NILAI HISTORISWAYANG BEBER KYAI REMENG - dan Aditya A. Christian, Lita Sahtila, Galuh Ambar Sasi, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
Kyai Remeng Puppets are a part of beber puppets in Orchard GelaranII, Bejiharjo Countryside, Karang Mojo Subdistrict, Gunung Kidul. This storytells about the incognition of pennon Asamara Bangun as Kyai RemengMangunjaya.This article analyzes the symbolic meaning and historical value oftotally dissapeared puppets. The symbolic aspects which are analyzed in thisresearch cover the activity done by the one who has the intention, role aspuppets, gamelan drummer, and sinden (woman singer with gamelanorchestra).The historical value in this story covers the comparative study of KyaiRemeng Beber Puppets in the past and in the present time. This study isimportant in showing the society participation in conserving the highlyvalued arts.Key Words: Beber Kyai Remeng puppets, symbolic meaning, historical value